RANCANG BANGUN SISTEM APLIKASI AKTIVITAS GURU DALAM PEMBELAJARAN BERBASIS ANDROID DI SMP AL- HIKMAH BALONGREJO - Oktavianto, Yusril; Imam Agung , Ahmad (Inovate, 2023)
The purpose of this research is to increase the credibility of work and the educational process, SMP Al-Hikmah Balongrejo plans to start improving faculty administration by implementing application-based technology and information to support school programs and student education. So to overcome this problem a teacher activation system is needed in teaching in the form of online and application-based. This application is able to summarize the time and achievement of reporting with valid data. The purpose of this research is to know the design of teacher activities, to know their implementation and the level of implementation of the design of teacher activity application systems in Android-based learning at SMP Al-Hikmah Balongrejo. Completion of this practical work report has several research stages that are useful in supporting the preparation of practical work reports. The research method used is an experimental method with a quantitative research type. From this study, the following conclusions were obtained; The Teacher Activity Application System is designed to meet the needs of teachers and employees in processing attendance and journal data. The Teacher Activity Application System can automatically calculate the disciplinary percentage of teacher absences by applying the K-Means method. The Teacher Activity Application System has been tested on teachers and employees to process attendance and journal data. Keywords: Teacher Activity, Application System, Android.